Litter Dynamics and Nutrient Contributions in Arabica Coffee Agroforestry Systems Under Varied Shade Regimes in the Central Western Ghats, India - Rudragouda; Girijesh, G. K.; Nagaraja, J. S.; Veeranna, H. K.; Adivappar, Nagarajappa; Devagiri, G. M.; Dinesh Kumar, M.; Nadaf, S. A.; Suchitra, M. A. (European Journal of Applied Sciences, 2025)
Coffee agroforestry systems (CAS) are increasingly recognized as an effective climate change mitigation strategy due to their ability to sequester carbon. However, most studies on CAS have focused on the management and productivity of coffee plants, with limited attention to litterfall dynamics and their contribution to soil nutrients, particularly in Indian coffee plantations. In this study, quantified and compared litterfall dynamics in arabica coffee (Coffea arabica L.) grown under different shade patterns. Litterfall collected from designated quadrants was analyzed using standard soil testing procedures. Results showed significant variation in litterfall across treatments, ranging from 3.43 to 13.54 MT ha-1. The highest litterfall was recorded under exotic species shade with 13.54 MT ha-1, followed by native species shade with 11.68 MT ha-1. In terms of nutrient contributions to the soil, coffee grown under native species shade recorded the highest addition of nitrogen (301.37 kg ha-1) and phosphorus (22.19 kg ha-1), significantly exceeding other treatments. Conversely, potassium addition was highest under exotic species shade (257.30 kg ha-1). The findings suggest that coffee grown under a two-tier mixed shade system, comprising both native and exotic species, benefits from enhanced litterfall dynamics and improved nutrient contributions to the soil compared to unshaded systems. To promote soil health and sustainability, policy incentives should encourage the adoption and maintenance of two-tier mixed shade systems in coffee plantations.